ENHANCING ELECTRICAL AUTOMOTIVE PROJECT DESIGN SKILLS WITH A CONTEXTUAL APPROACH - Henry Iskandar; Selamat Triono; Hidir Efendi; Lisyanto; Dwiki Muda Yulanto (Jurnal Pendidikan Teknik Mesin, 2024)
Learning innovations integrating the latest scientific theory sources emphasize the importance of students' technical skills in facing the transformation of Industry 4.0 technology. This study aims to determine the improvement of technical skills with the SAM (Successive Approximation Model) instructional design approach in Automotive Electrical and Electronics Engineering (AEEE) courses based on Industry 4.0. In this study, 20 respondents were divided into three groups. The SAM model is used as a practical learning instruction. The study results show that the SAM instructional design can improve students' abilities in analyzing, thinking critically, and solving problems. However, soft skills are obstacles, such as communication, action, and Emotional management skills. Student demographic data and pretest data compared to satisfaction data show a significant increase. Thus, the SAM instructional design is effective as one of the strategies for improving students' technical skills. This implication can reference more structured and directed skill passport learning.